Barriers and enablers to the implementation of person-centred care in an Indonesian hospital: a qualitative study - Dewi, Wan Nishfa; Nazriati, Elda (Universitas Airlangga, 2024)
Introduction: Person-centred care (PCC) is increasingly considered as one of the criteria standards for delivering healthcare in hospitals. Registered nurses are increasingly expected to provide PCC in daily practice. However, although the hospital commits to enhancing and improving PCC, implementing this approach into practice has faced barriers and enablers. As the implementation of PCC is still at an early stage of development, it is well-recognised that the need to identify barriers and enablers is essential. This study aims to explore these barriers and enablers to implementing PCC in Indonesian hospitals. Methods: This study employed a qualitative exploratory study conducted from July 2023 to September 2023 at a public hospital in Pekanbaru, Riau Province. It applied semi-structured interviews to collect data on barriers and enablers to implement PCC from 2 managers and 12 nurses from the medical ward. All participants were selected using a purposive sampling technique. Data collected from interviews were transcribed and then thematically analysed. Results: Three barriers-related themes emerged, namely time constraints and workload, lack of resources, and communication challenges. Furthermore, three enablers themes also emerged, including leadership, commitment, and sufficient monitoring and supervision. Conclusions: The study results lead hospital managers and policymakers to overcome existing barriers using adaptive planning and strategies and to improve enablers with well-trained professionals and strong leadership to deliver a PCC approach into practice. The implications to practice are that healthcare organisations must continue their support to decrease the barriers and optimise professional care in healthcare facilities to improve healthcare services.